Supervised Internship in Geography: reflections on teacher education / Estágio supervisionado em Geografia: reflexões a formação docente - Quitéria da Silva de Sá; Ricardo Santos de Almeida (Universidade Estadual de Alagoas, 2019)
We seek with this experience report to problematize the didactic-pedagogical experiences developed not during the supervised internship in two public schools (one municipal and one state) in Pariconha / AL between 2018 to 2019. For such, we look at for understanding the importance of didacticpedagogical planning establishing in it the valuation for learning that will enable in the teaching-learning relationship the socialization of didactic-geographic knowledge embodied in the normative documents of Brazilian education as the Law of Guidelines and Bases of National Education, and Also from the discussions of Freire (1996), Kaercher (2002), Lima and Pimenta (2005/2006), Callai (2011), Oliveira (2015), Rodrigues (2015) we will reflect the relationship of construction and reaffirmation of the teaching identity. based on operational strategies beyond knowledge of the school space and the classroom, but also to socialize some content, concepts and themes reaffirming the importance of geographic education.